Contrast‐enhanced voiding urosonography (CEVUS) as a safe alternate means of assessing vesicoureteral reflux in pediatric kidney transplant patients. (7th November 2022) - Cheng, Julie W.; Fernandez, Nicolas; Kim, Helen H. R.; Tang, Elizabeth R.; Ferguson, Mark; Nicassio, Lauren N.; Dick, André A. S.; Smith, Jodi M.; Cain, Mark P.
Abstract: Background: Although voiding cystourethrogram (VCUG) is currently the gold standard in VUR evaluation, there is ionizing radiation exposure. Contrast‐enhanced voiding urosonography (CEVUS) uses ultrasound contrast agents to visualize the urinary tract and has been reported to be safe and effective in VUR evaluation in children. CEVUS application has yet to be specifically described in VUR evaluation in the pediatric kidney transplant population. The purpose of this study was to report the use of CEVUS and VCUG in evaluating and managing VUR in pediatric renal transplant patients. Methods: Retrospective review was conducted for pediatric kidney transplant patients (18 years and younger) who underwent VCUG or CEVUS to assess for transplant VUR from July 2019 through June 2021. Demographic information, reason for VUR evaluation, fluoroscopy time, and postimaging complications were evaluated. Costs of imaging modalities were also considered. Results: Eight patients were evaluated for transplant VUR during the study period. Of the 3 patients who underwent VCUG, all 3 had VUR (median grade 3). Median fluoroscopy time was 18 s and dose‐area product was 18.7 uGy*m 2 . Of the 5 patients who underwent CEVUS, 4 had VUR (median grade 4). There were no complications for either modality. Based on clinical and radiographic findings, patients were recommended no intervention, behavioral modification, or ureteral reimplantation. The total cost of CEVUS was 800 less than that of VCUG. Conclusion: CEVUS can provide an alternate means of safely evaluating VUR in kidney transplant patients with similar outcomes, potentially lower costs, and no exposure to ionizing radiation.